Citrus By-Products as a Valuable Source of Biologically Active Compounds with Promising Pharmaceutical, Biological and Biomedical Potential - Silvija Šafranko; Drago Šubarić; Igor Jerković; Stela Jokić (MDPI AG, 2023)
Citrus fruits processing results in the generation of huge amounts of citrus by-products, mainly peels, pulp, membranes, and seeds. Although they represent a major concern from both economical and environmental aspects, it is very important to emphasize that these by-products contain a rich source of value-added bioactive compounds with a wide spectrum of applications in the food, cosmetic, and pharmaceutical industries. The primary aim of this review is to highlight the great potential of isolated phytochemicals and extracts of individual citrus by-products with bioactive properties (e.g., antitumor, antimicrobial, antiviral, antidiabetic, antioxidant, and other beneficial activities with health-promoting abilities) and their potential in pharmaceutical, biomedical, and biological applications. This review on citrus by-products contains the following parts: structural and chemical characteristics; the utilization of citrus by-products; bioactivities of the present waxes and carotenoids, essential oils, pectins, and phenolic compounds; and citrus by-product formulations with enhanced biocactivities. A summary of the recent developments in applying citrus by-products for the treatment of different diseases and the protection of human health is also provided, emphasizing innovative methods for bioaccessibility enhancements (e.g., extract/component encapsulation, synthesis of biomass-derived nanoparticles, nanocarriers, or biofilm preparation). Based on the representative phytochemical groups, an evaluation of the recent studies of the past six years (from 2018 to 2023) reporting specific biological and health-promoting activities of citrus-based by-products is also provided. Finally, this review discusses advanced and modern approaches in pharmaceutical/biological formulations and drug delivery (e.g., carbon precursors for the preparation of nanoparticles with promising antimicrobial activity, the production of fluorescent nanoparticles with potential application as antitumor agents, and in cellular imaging). The recent studies implementing nanotechnology in food science and biotechnology could bring about new insights into providing innovative solutions for new pharmaceutical and medical discoveries.